Provider-Level Risk-Adjusted Quality Measurement for Inpatient Rehabilitation Facilities - Dick, Andrew W. (RAND Corporation, 2012)
Quality metrics play an increasingly important role in the evaluation and reimbursement of post-acute providers. This report develops risk-adjusted quality measures at the provider level for inpatient rehabilitation facilities (IRFs), explores methods to address low case volume, and uses these metrics to estimate national trends in IRF quality from 2004 to 2009.